Evaluation of fracture resistance and mode of failure of premolars restored with nanohybrid composite, ORMOCER and ceramic inlays - Mohit. K. Gunwal; Pratima R. Shenoi; Tanvee Paranjape; Sonal Dhote; Ravish Tongya; Magesh Kumar; Sanjay Rastogi (Elsevier, 2018)
Objectives: To evaluate the fracture resistance and mode of failure of maxillary premolars restorations restored with nanohybrid Composite, ORMOCER and Ceramic Inlays. Materials and method: 100 extracted first maxillary premolar were collected. Samples were divided into five groups. Group I - Intact premolars, Group II -MOD cavities without restorations, Group III - MOD cavities restored with composite restoration, GROUP IV - MOD cavities restored with ORMOCER restoration and GROUP V - MOD cavities restored with ceramic inlays. All the samples were sent for the axial compression test under the universal testing machine. Fracture resistance and fracture modes were recorded. Result: Highest fracture resistance was achieved in Group V (1324.74 ± 336.78) almost comparable to that of natural tooth (1381.07 ± 259.36) (p < 0.05), followed by Group IV (MOD cavities with ORMOCER restorations) (1082.27 ± 351.27) (p < 0.01) and least fracture resistance in Group III (MOD cavities with composite restorations) (778.35 ± 100.25) (p < 0.0001). Mode of fracture in Group IV and Group V are almost similar and In Group III 65% of the cases showed non-restorable fractures. Conclusion: ORMOCER fracture resistance along with other groups of clinically restorable fracture stand better than Nanohybrid composite. Clinical Relevance: Based on the present study, the dentist can utilize the ORMOCER material as a restoration material for the cavities of posterior teeth which is better in terms of fracture resistance and durability of the restoration when compare to nanohybrid composite.